Changes in the activity of selected muscles during deep squat correction - Samuel Králik; Denis Freundenfeld; Daniel Gurín (Matej Bel University, 2021)
Background: Deep squatting, as part of postural ontogenesis, is an integral part of every athlete's training. Squats performed with the correct kinesiological pattern can ensure optimal loading of the musculoskeletal system, affect the function of the diaphragm and thus breathing in addition to positively affect the pelvic floor muscles. On the contrary, in the case of insufficient coordination, we can detect a failure in the stabilization of individual segments. Aim: The aim of the study was to find out the difference in the quality of muscle involvement in two variants of squats. The first squat was natural for an athlete without the intervention of a therapist, and in the second one we tried to adjust the individual segments biomechanically correctly. Methods: The group included 20 athletes, with an average age of 21.85 years. The measurement took place in the MSC Dukla Banská Bystrica building at a uniform time from 10:00AM to 12:30PM. We used a biomedical telemetry system with surface EMG. M. biceps femoris, m. semitendinosus, m. vastus medialis and m. erector spinae were measured. Results: The activity of the muscles on the back of the thigh showed lower average values after squat correction by physiotherapist instructions (significant in one case). Differences in activity of all muscles: m. biceps femoris dx (p = 0.16005), sin (p = 0,00268), m. semitendinosus dx (p = 0.838), sin (p = 0.0852). m. vastus medialis dx (p= 0.35), sin (p = 0.0066), m erector spinalis dx (p = 0.118), sin (p = 0.0632). Conclusion: Our measurements showed that the correction of individual segments to the correct biomechanical position was statistically confirmed in two cases (vastus medialis sin. and m. biceps femoris sin.), But from a practical point of view we recorded a positive effect on average muscle activity. and overall squat execution efficiency. DOI: https://doi.org/10.24040/sjss.2021.7.1.37-47